Front Cover: How Comparable are Microbial Electrochemical Systems around the Globe? An Electrochemical and Microbiological Cross‐Laboratory Study (ChemSusChem 11/2021). Issue 11 (20th May 2021) - Santoro, Carlo; Babanova, Sofia; Cristiani, Pierangela; Artyushkova, Kateryna; Atanassov, Plamen; Bergel, Alain; Bretschger, Orianna; Brown, Robert K.; Carpenter, Kayla; Colombo, Alessandra; Cortese, Rachel; Erable, Benjamin; et al.
Abstract : The Front Cover shows a sketch of a microbial fuel cell and a target indicating the need of developing common standards for the field of microbial electrochemical technologies. More information can be found in the Full Paper by C. Santoro, S. Babanova, P. Cristiani, et al .